Preferensi Generasi Z dan Milenial di Surabaya Terhadap Transportasi Mobil Online dengan Metode Conjoint - Pramonov, Quinneisha Zella; Saikhu , Ahmad (Jurnal Locus Penelitian dan Pengabdian, 2025)
Transportation services play a crucial role in facilitating mobility and supporting urban economic activities. The growing popularity of online car transport services such as Gocar, Grabcar, Maxim Car, and Bluebird reflects shifting consumer behavior, especially among digital-native generations. This study aims to analyze the preferences of Generation Z and Millennials in Surabaya toward online car transportation services. Using Conjoint Analysis, this research evaluates the relative importance of eight service attributes: price, promotion, customer trust, brand image, safety, responsibility, reliability, and tangibility. Primary data were collected from 120 respondents through an online questionnaire. The results reveal that customer trust and brand image are the most influential attributes for both generations. Generation Z tends to value innovation, credibility, and brand trust, while Millennials show stronger preferences for competitive pricing and promotional offers. Attributes such as safety and reliability are also considered, though to a lesser extent. These findings provide valuable insights for online transport service providers in developing targeted marketing strategies and improving service quality based on generational preferences. Understanding what each generation values most allows companies to enhance user satisfaction and competitiveness in the increasingly crowded ride-hailing market.